TESS hunt for young and maturing exoplanets (THYME). VI. an 11 Myr giant planet transiting a very-low-mass star in lower centaurus crux - Mann,AW; Wood,ML; Schmidt,SP; Barber,MG; Owen,JE; Tofflemire,BM; Newton,ER; Mamajek,EE; Bush,JL; Mace,GN; Kraus,AL; Thao,PC; et al. (The Astronomical Journal, 2022)
Mature super-Earths and sub-Neptunes are predicted to be Jovian radius when younger than 10 Myr. Thus, we expect to find 5–15 R⊕ planets around young stars even if their older counterparts harbor none. We report the discovery and validation of TOI 1227b, a 0.85 ± 0.05 RJ (9.5 R⊕) planet transiting a very-low-mass star (0.170 ± 0.015 M) every 27.4 days. TOI 1227's kinematics and strong lithium absorption confirm that it is a member of a previously discovered subgroup in the Lower Centaurus Crux OB association, which we designate the Musca group. We derive an age of 11 ± 2 Myr for Musca, based on lithium, rotation, and the color–magnitude diagram of Musca members. The TESS data and ground-based follow-up show a deep (2.5%) transit. We use multiwavelength transit observations and radial velocities from the IGRINS spectrograph to validate the signal as planetary in nature, and we obtain an upper limit on the planet mass of 0.5 MJ. Because such large planets are exceptionally rare around mature low-mass stars, we suggest that TOI 1227b is still contracting and will eventually turn into one of the more common <5 R⊕ planets.